To Build the Supervisory Capacity of the Regional Representative Council (DPRD) in Order to Realize the Implementation of Good Governance - H. M. Yasin; Nurmi Sari (Inovasi Pratama Internasional. Ltd, 2023)
The implementation of the supervisory function of the DPRD is mandated by law, supervision is intended to exercise control over the executive who is mandated to run the wheels of government in order to improve public welfare. But the supervisory function of the DPRD is a policy supervision rather than a technical one, the forms of supervision of the DPRD are in the form of hearings, work meetings, and monitoring and evaluation and field review, while absorbing the aspirations of the community related to government services and policies. It is not intended to create a good government.